PENERAPAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 012 CANDIREJO KECAMATAN PASIR PENYU KABUPATEN INGRAGIRI HULU - Elismawati, Elismawati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This classroom action research was motivated by the low mathematics learning outcomes of class I students, with a class average of 56.25. The purpose of this research was to improve the mathematics learning outcomes of first-grade students at SD Negeri 012 Candirejo Kecamatan Pasir Penyu through the Application of a contextual Teaching Model. The subjects of this study were a class I students totaling 17 people. The results of research in class I SD Negeri 012 Candirejo Kecamatan Pasir Penyu proved that the Application of contextual Teaching Model can improve mathematics learning outcomes in the pre-cycle average value of students is 56.25 in cycle I increased to 67.5 and in cycle II increased to 82, 5.